The Effect of Enamel Protective Agent on Shear and Tensile Bond Strength of Stainless Steel Brackets by Using Different Adhesive Agents (In Vitro Study) - AbdulQader, Dhuha; AlJoubori, Sami K (Journal of Baghdad College of Dentistry, 2017)
Background: Decalcification of surface enamel adjacent to fixed orthodontic appliances, in the form of white spot lesions, is a wide spread and familiar well-known side effect of orthodontic treatment. The present study was carried out to evaluate the effect of enamel protective agent (Clinpro white varnish) on shear and tensile bond strength of Dentaurum orthodontic stainless steel brackets by using 3M Unitek and Ormco as orthodontic adhesive agents. Materials and methods: Sixty-four extracted human upper first premolar teeth were selected and randomly divided into two groups with 32 teeth each, representing the shear and tensile bond strength testing groups. Then according to the type of bonding adhesive and the addition of Clinpro before bonding (3M, Clinpro + 3M, Ormco, Clinpro + Ormco) each group was subdivided into four equal subgroups each with 8 teeth. After passing twenty-four hours of bonding procedure, where the samples were kept at 37ËšC the brackets were debonded by using Tinius-Olsen universal testing machine to record the shear and tensile bond strength value. The difference in bond strength was analyzed by using ANOVA test at pâ‰¤0.05. Results: The use of Clinpro with 3M Unitek orthodontic bonding agent shows higher shear and tensile bond strength than Clinpro with Ormco orthodontic bonding agent. Conclusions: Using Clinpro white varnish before bonding can be successfully used with 3M Unitek orthodontic bonding agent.